The Influence of the Court of Justice of the European Union on the Issuance of European Arrest Warrants in Lithuania - Milčiuvienė Saulė (Baltic Journal of Law & Politics, 2019)
The European arrest warrant system is one of the greatest achievements in the development of cooperation in judicial matters among EU Member States. However, its implementation has raised many questions, resulting in referrals by national courts to the Court of Justice of the European Union (CJEU) for preliminary rulings. This article analyses the impact of the CJEU’s preliminary rulings on Lithuanian law concerning European arrest warrants. Specifically, the focus of the paper is institutional configuration and corresponding regulation in this field because/after the CJEU decided that (1) the Ministry of Justice cannot be considered a judicial authority because as part of the executive branch it cannot guarantee the protection of the parties’ fundamental rights; (2) however, the Prosecutor General of Lithuania can be considered a judicial authority because it participates in the administration of criminal justice and is independent of executive governance, and because its decisions to issue European arrest warrants are subject to judicial review.